2012
DOI: 10.1007/s12288-012-0216-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD20 in B Cell Precursor Acute Lymphoblastic Leukemia

Abstract: CD20 is a B cell differentiation antigen with variable expression in B cell precursor acute lymphoblastic leukemia (BCP-ALL). The significance of CD20 expression has been evaluated in BCP-ALL with conflicting results. There is paucity of data regarding CD 20 expression in BCP-ALL in Indian patients. We retrospectively analyzed 100 patients of BCP-ALL for CD20 expression. CD20 positivity was defined as expression of CD20 to be more than or equal to 20 % in the blast population. 62 % patients expressed CD20 whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Another significant observation was the higher rates of CD20 expression found in children compared to adults. Some studies have reported expression of CD20 in nearly half of childhood and a quarter of adult B‐ALL, although other studies have not revealed any differences in these two age groups …”
Section: Discussionmentioning
confidence: 98%
“…Another significant observation was the higher rates of CD20 expression found in children compared to adults. Some studies have reported expression of CD20 in nearly half of childhood and a quarter of adult B‐ALL, although other studies have not revealed any differences in these two age groups …”
Section: Discussionmentioning
confidence: 98%
“…In our cohort, CD20 was found to be positive in 53.5% (n=146/273) cases similar to that reported in Indian literature810 but higher than that reported in western literature (20–40%). These differences could be due to the choice of fluorochromes used in different studies 30…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CD20 is expressed only in a small subset of precursor B cells [31]. Expression of cyt IgM and immaturity antigens (e.g.…”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%